Alternative caregivers` role in food choices for young children in semi-urban and urban Mexico. Issue 6 (2nd November 2022) - Armendariz Aguirre, Gabriela C.; Frongillo, Edward A.; Reyes, Ligia I.; Bonvecchio, Anabelle; Blake, Christine E.
ABSTRACT: Alternative caregivers (i.e., someone besides the primary caregiver who also takes care of children) make food choices for children. This study investigated what alternative caregivers consider when making food choices for children and their perspectives on their role in making food choices to feed children. In-depth interviews were conducted with 16 alternative caregivers of children aged 1–5 years old in semi-urban and urban areas of the State of Mexico in Mexico. Interviews were recorded, transcribed, coded, and analyzed using constant comparative method. Alternative caregivers described spaces and situations that exposed children to food while under their care. Alternative caregivers who spent longer periods of time with the child described more involvement in what the child ate. Healthy or nutritious food, cost of food and affection for children were important considerations for alternative caregivers when deciding what to feed the child. Alternative caregivers had a substantial role in child feeding, decisions about cooking, and advising mothers on how to feed their children. Efforts to promote healthy food choices for children should include targeting of alternative caregivers.